A educação no trabalho no contexto da estratégia saúde da família - Demori, Renata Zanoni (Universidade Federal de São Carlos, 2015)
The challenges to be overcome by the Family Health Strategy, educational activities at work that are developed daily, may contribute to the transformation of practices with incorporation of new health values, closer to what the SUS proposes. In this sense, there is a permanent education that emerge from questioning and the work process reflection to reframe the professional practice. Objectives: This study aims to analyze the concepts and practice of educational activities at work developed by doctors, nurses and dentists in the context of the Family Health Teams. Methodology: This is an exploratory, descriptive qualitative study by joint interview, semi-structured, among nurse, doctor and dentist managers fourteen Family Health Teams of São Carlos - SP. For data analysis was used content analysis proposed by Bardin (1977).Analysis: data analysis allowed the construction of four categories: 1st - Understanding of Education at Work, which brought the examples were closer to the concept of Continuing Education; 2nd -Teaching Basement in Educational Practice, some subjects reported understand learning as transmission of knowledge, some as work questioning; 3rd - Educational Spaces in the Family Health Teams, especially the team meetings, although an appreciation of technical skills; 4th - Support of Municipal Management, in which subjects reported little support from management. Conclusion: Education at work has been discussed and used by the teams. Note is an effort to fit the educational proposals more reflective and problem-solving, highlighting the contributions received by the closeness to the university.
Keywords: Educação Profissional em Saúde Pública; Aprendizagem; Saúde da Família; Public Health Professional; Learning; Family Health; Professional Practice; CIENCIAS DA SAUDE::MEDICINA